In Vitro Seed Germination and RAPD Variation in Three Populations of Cerastium candidissimum Correns, a Promising Ornamental Species - Konstantinos Bertsouklis; Stella Tsopela; Apostolos-Emmanouil Bazanis; Epameinondas Kartsonas (Horticulturae)
This study investigated the germination characteristics and genetic variability of Cerastium candidissimum, a Greek endemic species with potential for ornamental horticulture. The seeds were collected from three populations of Mount Hymettus, M. Parnitha, and M. Parnassos. The cardinal temperatures for germination, the effect of seed storage duration, and population-specific germination responses were examined. Germination trials were conducted in vitro on half-strength Murashige and Skoog medium, with seeds tested after dark and dry room storage periods of 6, 18, and 30 months. Seeds from Mount Parnitha exhibited high germination rates (81–94%) within a temperature range of 10–20 °C after 6 and 18 months of storage. Similarly, seeds from Mount Parnassos demonstrated optimal germination (81.3–94.0%) at 10–20 °C after 6 months of storage, though an 18-month storage period shifted the optimal range to 15–20 °C (67–71%). In contrast, the Mount Hymettus population exhibited the lowest germination percentages, with 6-month-old seeds reaching only 47.3% germination at 20 °C, declining to 34% at 15 °C after 18 months, and near-zero germination after 30 months. The time required for 50% germination (T50) ranged from 4 to 8 days at 20 °C across all populations but increased as incubation temperature decreased (4–18 days at 15 °C; 8–18 days at 10 °C). The molecular analysis revealed that the primers used presented high polymorphism (49.0%), and a total of 136 amplified markers were produced. Individuals from different populations were grouped in three different branches. These findings indicate population-level variability in germination traits, likely reflecting genetic and ecological differences. The high germination rates of Parnitha and Parnassos’ populations support their potential use in floriculture. Conversely, the low germination success of the Hymettus population suggests higher environmental stress or genetic constraints, warranting further investigation into its possible classification as a distinct ecotype.